EFFECTS OF SCULPTRA® (INJECTABLE POLY-L-LACTIC ACID) FOR FACIAL REJUVENATION:: A SYSTEMATIC REVIEW - Diógenes Guimarães de Lima Menezes, Eduarda; Costa, Ana Carolina de Figueiredo; de Sousa Neto , José Bonifácio; Maques, Joyce Alves; Santos, Marcelo Januzzi (Health and Society, 2022)
Poly-L-lactic acid (PLLA) is a synthetic, biocompatible and biodegradable polymer of the alpha-hydroxy acid family. This substance has provided satisfactory and safe results in several medical applications in the last three decades. The brand name Sculptra® has been widely investigated in the area of facial cosmetics. The aim of this study was to performed a systematic review of the effects of Sculptra® for facial rejuvenation. This review was registered on the prospero platform under protocol CRD42021277434. A careful search was conducted in the Pubmed, Scopus, BVS, Scielo, Web of Science, LILACS and Cochrane Library databases up to February 2021. Gray literature was consulted at Open Grey. In addition, a manual search was performed. Clinical studies were selected, without restriction of publication date or language. Data synthesis and risk of bias assessment of the included studies was performed by two independent authors. Eight clinical studies were selected for data synthesis (three randomized clinical trials, two prospective cohorts and three retrospective cohorts). Data synthesis demonstrated that Sculptra® is considered an effective, safe and long-acting agent for collagen volumization and biostimulation. The assessment of the risk of bias of the RCTs revealed a low risk of bias in all domains, with the exception of the domain of concealment of allocation of participants. Within the limitations of the systematic review, the use of Sculptra® for facial rejuvenation is effective, safe and long-lasting.